2019
DOI: 10.21857/9xn31crexy
|View full text |Cite
|
Sign up to set email alerts
|

High-fat Diet Induced Dysbiosis & Amelioration by Astaxanthin

Abstract: Astaxanthin is a carotenoid that is present in high quantities in the meat of fish like salmon and the shells of shrimp and crab. It exhibits free radical scavenging antioxidant activity when consumed dietarily. Astaxanthin is absorbed by the small intestine before exerting its antioxidant effect; however, a portion of dietary intake remains unabsorbed in the digestive tract and reaches the large intestines. We hypothesized that astaxanthin may exert its antioxidant action in the large intestine to influence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Moreover, this increase is not observable in the group supplemented with HMH2, which is the same supplement as HMH3 without astaxanthin. Although some in vivo studies have looked at the effect of astaxanthin on certain genera of Actinobacteria , such as Bifidobacteria , to date no work has yet shown that astaxanthin has a pre-biotic effect on this phylum or many of its genres [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, this increase is not observable in the group supplemented with HMH2, which is the same supplement as HMH3 without astaxanthin. Although some in vivo studies have looked at the effect of astaxanthin on certain genera of Actinobacteria , such as Bifidobacteria , to date no work has yet shown that astaxanthin has a pre-biotic effect on this phylum or many of its genres [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…While astaxanthin is one of the fatsoluble components, its increased rate of absorption is attributable to the fact that it is more polar than the other carotenoids. I'm not the only one who thinks so; research suggests that astaxanthin helps the body digest food and absorb more nutrients by raising the number of helpful microorganisms [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Astaxanthin has also been found to exert anti-glycation effects [ 36 , 37 ]. Previous work in the lab has examined the effects of dietary astaxanthin intake in both animal and human models; astaxanthin was found to ameliorate high fat diet induced gut dysbiosis in mice, and improved reported gastro-intestinal symptoms in human participants [ 38 ].…”
Section: Discussionmentioning
confidence: 99%